Modeling leg and mono-fin movements technique using a neuronal network in consecutive stages of swimming cycle - Rejman, M. (First international symposium sciences and practices in swimming, 2006)
The aim of the study is to verify the diagnostic value of modeling the mono-fin swimming technique by means of artificial neural networks in order to optimize the technique of legs and mono-fin movements. The practical aspect of the modeling of the mono-fin swimming technique is apparent since the Interpretation of the propulsion as such is much less complicated than it is in the case of traditional swimming. Assuming that the technical level of the swimmers participating in the study is high (elimination of redundant degree of freedom in the chain swimmer's body-mono-fin) the analysis was limited to the lower thigh, foot and mono-fin movements. The model of the neural network allowed identifying the differences in the structure of the movements phases, pointing to extra margin that can be used to generate propulsion while making an upward movement and, simultaneously, paving the way to optimize the mono-fin swimming technique